NETWORK MODEL AND ALGORITHM FOR SOLVING PROBLEM PERTAINING TO OPTIMUM DISTRIBUTION OF CAPITAL INVESTMENT WHILE MODERNIZING ENTERPRISES OF HEATING SYSTEMS - V. A. Sednin; A. D. Korznikov; А. V. Sednin (Наука и техника)
The paper presents a problem statement, a developed mathematical model and proposed algorithm for  solving  optimization of capital  investments in modernization  (introduction of  automatic  controlsystems of thermal processes) of large systems of centralized heat supply which are based on application of network model.The formulated problem refers to the problems of combinatory (discrete) optimization. Methods of «branches and boundaries» or dynamic programming are applied nowadays for solving problems of this type. These methods are not considered as universal ones because they greatly depend on description  of  solution feasible area. As a result of it it is not possible to develop a universal software for solving any assignments which can be formulated as problems of combinatory optimization.The presented network model of the investigated problem does not have above-mentioned disadvantages and an algorithm is proposed for solving this problem which admits a simple programming realization.